Microbial Inoculum Composition and Pre-weaned Dairy Calf Age Alter the Developing Rumen Microbial Environment - Cersosimo, Laura M.; Radloff, Wendy; Zanton, Geoffrey I. (Frontiers in Microbiology, 2019)
The objective of this experiment was to determine if microbial inoculum composition alters the rumen microbial ecology and performance of pre-weaned dairy calves. Twenty Holstein bull calves were removed from their dam at birth, fed 3.8 L colostrum within 1-4 hours after birth, and housed individually. Calves were fed pasteurized milk 3x/d and offered a texturized calf starter ad libitum at 6d of age. A randomized complete block design with repeated measures and a 2 x 2 factorial arrangement of treatments was used to evaluate responses. Treatments were administered by stomach intubation and included: 50 mL autoclaved rumen fluid (RF), 50 mL bacterial-enriched RF (BE), 50 mL protozoal-enriched RF (PE); or 50 mL of each BE and PE inoculum. A rumen content composite was collected from 4 rumen fistulated, lactating Holstein cows. BE inocula were microscopically confirmed to be free of ciliate protozoa before inoculation, while PE contained 2.9±2.2 x 105 protozoa/mL. RF was collected from the calves and inocula were administered once/week at 3-6 weeks of age by stomach intubation. pH and total volatile fatty acid concentration of the PE inocula were greater than BE inocula (P<0.001). PE inoculum (3.7±0.5 mM) had lower NH3 concentrations than BE inoculum (6.8 mM). The bacterial community structure and composition differed by inocula type (P<0.01). Animal performance was not altered by inocula type. All calves were microscopically free of rumen ciliates at 3 weeks of age and calves that did not receive PE remained ciliate-free. Ciliate protozoa were observed in RF from 6, 8, and 6 PE calves (n=10) at week 4, 5, and 6, respectively. Ruminal NH3 was lower in PE calves (3.3 vs 6.8±1.0 mM), while ruminal butyrate molar percent was greater in BE calves (10.8 vs 8.3±0.8). Rumen bacterial diversity measures did not differ by treatment. Individual calf bacterial communities from treated calves became temporarily similar to the inocula, but these communities diverged from the inocula prior to the last inoculation. This study provides new information about two types of rumen-derived inocula and insight into the challenges of directing the rumen microbial environment in the pre-weaned calf.